Salmonella carriage by geckos detected within households in Malawi - Wilson, C.N.; Musicha, P.; Beale, M.A.; Diness, Y.; Kanjerwa, O.; Salifu, C.; Katuah, Z.; Duncan, P.; Nyangu, J.; Mungu, A.; Deleza, M.; Banda, L.; et al. (Elsevier, 2024)
Salmonella was isolated from 23/79 (29.1%) pooled gecko stool samples from households in southern Malawi. Whole genome sequencing of 47 individual isolates within this collection revealed 27 Salmonella serovars spanning two subspecies. Our results demonstrate that geckos play an important role in the carriage of Salmonella within households.